Impact of Stocking Density and Culture Medium on the Life Table Parameters of Moina Macrocopa - Omdevsinh J. Vala (KUFOS, 2019)
Abstract- Cladocerans are commonly known as ‘water flea’. Cladocerans are successfully utilized in the aquaculture as food for larval fish and most preferred by many fish larvae due to their jerky movement and make them more visible to fish larvae. The present study has been planned to determine the growth, longevity, fecundity of Moina by using cottonseed oil cake, gingelly oil cake and rice bran. The growth of Moina at four different stocking densities (10, 15, 23, 45 ind./450 ml) and life span and fecundity were determined. The highest growth of adult was 36 ind./ml on 3rd day in 0.5 level feeding in yeast in 45 stocking density and the lowest growth was 27.33 ind./ml in 0.5 level feeding in CSOC in 23 stocking density was recorded on 3rd day respectively. Subsequently the highest and the lowest growth of juvenile was 51.67 ind./ml in yeast in 15 stocking density at 4th day and 35.33 was recorded in CSOC in 23 stocking density and 10th day respectively. Likewise, for neonates the highest growth was 88.67 ind./ml on 4th day in yeast in 0.5 level feeding in 45 stocking density and the lowest was 83 on 4th day in RB in 0.5 level feeding in 45 stocking density was recorded respectively. The longevity of Moinawas highest in RB was 11.5 ± 0.70 and the lowest 9 ± 0 was recorded in yeast. Highest offspring born from a single was 60 ± 8.48 in yeast and lowest was 23.5 ± 0.70 in CSOC respectively. The highest reproduction peak was obtained 25 ± 2.82 in GOC and lowest 13.5 ± 3.53 was obtained in CSOC respectively.